Effects of sevoflurane and isoflurane on urea cycle and hepatic functions - Bayar, M.K.; Gursu, F.; Akin, M.; Onal, A.; Yayla, T. (My University, 1998)
Thirty four ASA I class patients aged between 19-45 years were included in the study. They were treated with 5 mg IM droperidole and 0.5 atropine for premedication, and anaesthesia was induced via infusion of 2 mg/kg propofol and 0.1 mg/kg vecuronium. The patients were randomly scheduled for 2 groups and during the maintenance of anaesthesia 50 % O2+50 % N2O was accompanied with 2 % sevoflurane and 1.5 % isoflurane for the first and second groups respectively. Arginase, ALT - AST, urea, creatinin levels were measured in the baseline, 60-120th minutes for anaesthesia and postoperative 6th, 12th, 24th hours. Arginase levels increased in both groups. Urea levels slightly increased during anaesthesia in group II whereas a considerable change did not occur in group I patients. There were increases in ALT and AST levels but without a remarkable difference between the two groups. It was concluded that although sevoflurane having higher hepatic metabolism than isoflurane can lead to slight increases in the arginase level but has no significant effects on the hepatic function.
Sevofluran ile isofluranin ure dongusu ve karaciger fonksiyonlari uzerine etkileri
Keywords: Anaesthesia; Arginase; Hepatic functions; Isoflurane; Sevoflurane; Urea